Molecular Properties of Globin Channels and Pores: Role of Cholesterol in Ligand Binding and Movement - Morrill, Gene A.; Kostellow, Adele B. (Frontiers in Physiology, 2016)
ABSTRACT: Globins contain one or more cavities that control or affect such functions as ligand movement and ligand binding. Here we report that the extended globin family [cytoglobin (Cygb); neuroglobin (Ngb); myoglobin (Mb); hemoglobin (Hb) subunits Hba(α) and Hbb(β)] contain either a transmembrane (TM) helix or pore-lining region as well as internal cavities. Protein motif/domain analyses indicate that Ngb and Hbb each contain 5 cholesterol-binding (CRAC/CARC) domains and 1 caveolin binding motif, whereas the Cygb dimer has 6 cholesterol-binding domains but lacks caveolin-binding motifs. Mb and Hba each exhibit 2 cholesterol-binding domains and also lack caveolin-binding motifs. The Hb αβ-tetramer contains 14 cholesterol-binding domains. Computer algorithms indicate that Cygb and Ngb cavities display multiple partitions and C-terminal pore-lining regions, whereas Mb has three major cavities plus a C-terminal pore-lining region. The Hb tetramer exhibits a large internal cavity but the subunits differ in that they contain a C-terminal TM helix (Hba) and pore-lining region (Hbb). The cavities include 43 of 190 Cygb residues, 38 of 151 of Ngb residues, 55 of 154 Mb residues and 137 of 688 residues in the Hb tetramer. Each cavity complex includes 6 to 8 residues of the TM helix or pore-lining region and CRAC/CARC domains exist within all cavities. Erythrocyte Hb αβ-tetramers are largely cytosolic but also bind to a membrane anion exchange protein, “band 3”, which contains a large internal cavity and 12 TM helices (5 being pore-lining regions). The Hba TM helix may be the erythrocyte membrane “band 3” attachment site. “Band 3” contributes 4 caveolin binding motifs and 10 CRAC/CARC domains. Cholesterol binding may create lipid-disordered phases that alter globin cavities and facilitate ligand movement, permitting ion channel formation and conformational changes that orchestrate anion and ligand (O2, CO2, NO) movement within the large internal cavities and channels of the globins.